Situation Report: Romania, 6 November 1987 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu Admits Economic Failures, Eschews Responsibility / by Anneli Ute Gabanyi Nicu Ceausescu on the Way Up? / by Anneli Ute Gabanyi Romania's Strained Relationships with the CMEA / by Anneli Ute Gabanyi Romania's Uncomfortable Position between the EEC and the CMEA / by Mihai Sturdza Scanning the High Seas for Clients for the Danube-Black Sea Canal / by Vladimir Socor Welcome to Romania Housing as a Political Tool / by Dan Ionescu